Dementia and quality of life - Kisvetrová, Helena; Tylšarová, Helena (Palacký University Olomouc, 2020)
The publication focuses on dementia and the quality of life of people with dementia. It presents the results of research conducted in the years 2016-2019 in Czechia. Intended for the professional public.
Keywords: geriatrie; neurologie; prospektivní studie; Dementia; Longitudinal Studies; Quality of Life; dějiny 21. století; Prospective Studies; Česká republika; Biomedical Research; empirický výzkum; duševně nemocní; Empirical Research; Czech Republic; Persons with Psychiatric Disorders; sociologie; demence; kvalita života; longitudinální studie; Aged; History, 21st Century; biomedicínský výzkum; senioři